Schooling mobility across three generations in six Latin American countries - Pablo Celhay; Sebastian Gallegos (Journal of Population Economics, 2025)
This paper presents new evidence on schooling mobility across three generations in six Latin American countries. By combining survey information with national census data, we have constructed a novel dataset that includes 50,000 triads of grandparents, parents, and children born between 1890 and 1990. We estimate five intergenerational mobility measures, finding that multigenerational persistence in our six countries is twice as high as in developed countries, and 77% higher than iterating a two-generation model would predict. A theory of high and sticky persistence provides a better approximation for describing mobility across multiple generations in our sample. Even with high persistence, we uncover significant mobility improvements at the bottom of the distribution by estimating measures of absolute upward mobility and bottom-half mobility over three generations. This novel evidence deepens our understanding of long-term mobility, and we expect future research to replicate it as more multigenerational data becomes available in different contexts.
Keywords: J62; N36; O15; I24; I25; I28; 330; Developing countries; Latin America; Intergenerational mobility; Upward mobility; Multigenerational data; Reduced inequalities; Quality education; Educational persistence; Multigenerational mobility; Schooling mobility